OVARIAN DYSGERMINOMAS: TREATMENT EXPERIENCE OF THE N.N.BLOKHIN CRC RAMS - O. N. Streltzova; M. Yu. Fedyanin; A. A. Tryakin; A. A. Bulanov; V. V. Zhordania; S. A. Tyulandin (Опухоли женской репродуктивной системы, 2014)
This is a retrospective review of treatment results of 35 patients with dysgerminomas in the Departments of Clinical Pharmacology and Gynecology, N.N.Blokhin Russian Cancer Research Center (NNBRCRC) between 1990 and 2006.Primary surgery was carried out in all patients. Twenty patients (57%) underwent fertility-sparing surgery. Postoperative systemic chemotherapy was administered to 28 (80%) women: аmong them 23 received platinum-based chemotherapy, 5 were treated with non- platinum combinations.At a median follow-up of 75 months the disease-free survival was 71,4% and the overall survival was 97,1%. Our data confirmed that prog- nosis of dysgerminomas is excellent if managed with standard treatment initially, this is possible, as a rule, only in specialized cancer centers.